Pengaruh perceived usefulness dan perceived ease of use terhadap intention to use dengan attitude sebagai variabel intervening pada e-commerce Tokopedia di Yogyakarta - Migueli, Imer; Lukitaningsih, Ambar; Ningrum, Nonik Kusuma (Journal of Management and Digital Business, 2024)
The presence of the internet the previous several decades has brought about rapid changes in human lifestyle patterns in various aspects ranging from social, cultural, political, to economic. The internet's rising appeal offers up business opportunities with the concept of integrating the internet with commerce, which is called e-commerce. The purpose of this study was to investigate the relationship between perceived ease of use and usefulness on intention to use with attitude as an intervening variable at the Tokopedia online store in Yogyakarta. This study analyzed quantitative data. Population data from 160 participants were collected through a questionnaire method. The results showed that a person's perception of usefulness and ease of use greatly influenced their attitudes and their intention to use. The concept has a positive and significant impact on the desire to use. It was also added that attitude as an intervening variable can significantly affect the relationship between perceived usefulness and perceived ease of use on intention to use. The findings of this study can be useful in developing business strategies to increase customer intention to use Tokopedia e-commerce and face a competitive business environment.